2005
DOI: 10.1097/00124784-200503000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Turning Point and Public Health Institutes

Abstract: Public Health Institutes are free-standing multisector entities able to function as conveners to improve health status and foster innovations in health systems. Turning Point is a program funded by The Robert Wood Johnson Foundation, involving 21 statewide initiatives and 2 "linked" states that formed multisector collaborative partnerships for public health systems change. In 18 of the Turning Point states, there are also Public Health Institutes, some formed by Turning Point partnerships and some established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A 2005 assessment showed that 55 percent of local health agencies engage in some kind of formal performance assessment (Padgett et al, 2005). However, the most common type of data collected was customer satisfaction surveys.…”
Section: What Capacities Are Needed For Communities To Implement Commmentioning
confidence: 99%
“…A 2005 assessment showed that 55 percent of local health agencies engage in some kind of formal performance assessment (Padgett et al, 2005). However, the most common type of data collected was customer satisfaction surveys.…”
Section: What Capacities Are Needed For Communities To Implement Commmentioning
confidence: 99%
“…If the question of cost pressure is also taken into account, it becomes clear that greater structural complexity requires the definition of the principles of medical services planning and providing services in order to avoid unnecessary costs (Gibson, 1996;Padgett et al, 2005). An additional issue is to identify those areas in which synergies can be found and exploited in order to enable the installation of a higher-level strategically oriented cost and performance management system.…”
Section: Introductionmentioning
confidence: 99%
“…Medical networks can also arise for strategic reasons, for example, to enable change management processes to be planned and coordinated, or market situations to be dealt with in a coordinated way (Padgett et al, 2005;Thaldorf and Liberman, 2007). At this point, it should be noted that effectively and reliably networked institutions can also realise competitive advantage in the market (Tourigny et al, 2004).…”
Section: Introductionmentioning
confidence: 99%